Two-dimensional metal oxide composite reducing graphene oxide burn rate catalyst

CN120398629BActive Publication Date: 2026-10-16SHAANXI NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510557130.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-16
Estimated Expiration
2045-04-29

AI Technical Summary

Technical Problem

然而,这些纳米金属氧化物催化剂由于高表面能而容易聚集成大颗粒,不易控制其纳米粒子的尺寸,导致比表面积大大降低,从而降低了对含能材料的催化效果

Benefits of technology

[0017] 1. This invention combines two-dimensional metal oxide nanosheets and reduced graphene oxide via a solvothermal method, controlling the longitudinal scale of the metal oxide at the nanoscale to expose more surface active sites. Furthermore, the reduced graphene oxide used is surface-modified with surfactants, enabling better dispersion in water. In addition, the interaction between the surfactants and graphene functionalizes the graphene, facilitating further loading of two-dimensional metal oxide nanosheets. Combining this with two-dimensional metal oxide nanosheets increases the specific surface area and electron transfer rate of the composite combustion catalyst, thereby improving catalytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398629B_ABST
    Figure CN120398629B_ABST
Patent Text Reader

Abstract

The application discloses a two-dimensional metal oxide composite reduced graphene oxide burning rate catalyst, glucose, ammonium nitrate and transition metal nitrate are uniformly ground, then two-dimensional metal oxide nanosheets are generated by high-temperature calcination, then the two-dimensional metal oxide nanosheets are mixed with reduced graphene oxide powder modified by a surfactant, and are transferred into a high-pressure hydrothermal kettle to perform a solvothermal reaction, so that the reduced graphene oxide and the two-dimensional metal oxide nanosheets are compounded to form a 2D-2D structure composite burning rate catalyst. The two two-dimensional materials are compounded by the solvothermal method, the accumulation of the reduced graphene oxide and the aggregation of the two-dimensional metal oxide due to high surface energy are effectively avoided, meanwhile, the high conductivity of the reduced graphene oxide is utilized, the synergistic catalysis of the metal oxide and the carbon material is enhanced, and the composite material has a good catalytic effect on the catalysis of the ammonium perchlorate thermal decomposition process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid propellant technology, specifically relating to a combustion rate catalyst for two-dimensional metal oxide composite reduction of graphene oxide. Background Technology

[0002] Solid propellants are special energetic materials that provide power for missiles, rockets, and spacecraft. They consist of (modified) double-base propellants and (modified) composite solid propellants. Composite propellants, due to their simpler manufacturing process and greater flexibility in adjusting the propellant diameter, play a crucial role in various weapons such as rockets and missiles. Composite solid propellants are energetic materials formulated with various components including binders, oxidizers, high-energy combustion agents, combustion performance modifiers, plasticizers, stabilizers / anti-aging agents, and bonding agents. They possess advantages such as high energy density, excellent mechanical properties, relatively simple processing, and good safety performance, making them important in various weapons such as rockets and missiles. Combustion performance modifiers, also known as burning rate catalysts, are generally added to solid propellants to adjust the burning rate and reduce the pressure index, thereby lowering the temperature sensitivity coefficient of the burning rate within a certain temperature range and further improving the overall performance of the solid propellant. Therefore, adding burning rate catalysts to solid propellants is a very effective method.

[0003] Graphene has attracted extensive research due to its unique two-dimensional structure, large surface area, good electrical conductivity, high mechanical strength, light weight, and structural flexibility. In particular, chemically prepared reduced graphene oxide nanosheets are widely used as effective carbon support materials. In catalyst preparation, graphene can act as a dispersant, effectively inhibiting the aggregation of nanoparticles. Furthermore, the synergistic effect between graphene and nanoparticles further enhances the catalytic performance of the catalyst. In recent years, reduced graphene oxide supported catalysts have received considerable attention. Zhao Fengqi et al. prepared rGO@Fe2O3 composites using atomic layer deposition (ALD). Through surface chemical interactions, Fe2O3 nanoparticles were uniformly fixed on rGO nanosheets, achieving uniform dispersion of densely packed Fe2O3 nanoparticles. Compared with unsupported Fe2O3 nanoparticles, the spatial distribution of the composite material was improved, and the number of active sites increased. The results show that, with rGO@Fe2O3 (212%) as a catalyst, the high-temperature decomposition peak temperature of ammonium perchlorate (AP) is significantly lower than that of Fe2O3 without support, indicating that rGO as a support effectively inhibits the aggregation of Fe2O3 nanoparticles (Ning Yan, Lijun Qin, Jianguo Li, Fengqi Zhao, Hao Feng. Atomic layer deposition of iron oxide on reduced graphene oxide and its catalytic activity in the thermal decomposition of ammonium perchlorate[J]. Applied Surface Science. 2018, 451: 155-161).

[0004] Nanoscale metal oxides, especially transition metal oxides (TMOs), are traditional combustion rate catalysts, and their abundant and widespread distribution in nature has made them a hot research topic. The lattice defects and vacant electrons within the crystals of metal oxides provide numerous active sites for the reaction. These active sites can adsorb large amounts of oxidants and their decomposition products, thereby accelerating propellant combustion and decomposition. However, these nanoscale metal oxide catalysts are prone to agglomeration into large particles due to their high surface energy, making it difficult to control the size of the nanoparticles and resulting in a significant reduction in specific surface area, thus decreasing the catalytic effect on energetic materials. To avoid agglomeration, a special method is to construct hierarchical structures, i.e., uniform assemblies of nanomaterials. Studies have confirmed that such hierarchical structures can effectively maintain the size effect of nanocomposite structures, and their secondary structures can serve as a supporting substrate, possessing the dual advantages of anti-agglomeration and improved stability, both of which are key factors affecting catalytic activity. Zhang Wenchao et al. used MnCo2O... 4.5Vertically anchored on reduced graphene oxide, a hierarchical porous structure is formed. The introduction of reduced graphene oxide significantly increases the material's conductivity and specific surface area, effectively preventing the formation of MnCo2O. 4.5 The aggregation of nanoparticles and the recombination of graphene. The results show that MnCo2O 4.5 The synergistic effect between nanoparticles and reduced graphene oxide can promote electron capture and transfer, rGO / MnCo2O 4.5 The composite material caused the low-temperature decomposition peak of AP to disappear, reduced the high-temperature decomposition temperature by 124.1℃, and the reaction rate was 186.8 times that of pure AP. (Zilong Zheng, Wenchao Zhang, Liang Chen, Wenhui Xiong, Guowei Zeng, Jiaqi Liu, Runhui Wu, Jiaxin Wang, Jiahai Ye, Junwu Zhu, In-situ synthesis of MnCo2O) 4.5 nanosheets on reduced graphene oxide for a great promotion in the thermal decomposition of ammonium perchlorate[J].Applied Surface Science.2019,483:496-505).

[0005] Therefore, reduced graphene oxide has attracted much attention due to its large specific surface area, structural stability, and good conductivity, and as a highly efficient support, it shows great promise in the field of combustion catalysis. In addition, metal oxides possess good stability and numerous catalytically active sites. Controlling the thickness of metal oxides in the longitudinal direction to the nanoscale to form two-dimensional layered materials exposes more surface active sites, shortens electron transport channels, and increases the specific surface area of ​​the metal oxides, aiming to achieve better catalytic effects. However, the surface energy of two-dimensional layered metal oxides easily stacks and aggregates, leading to a decrease in the specific surface area of ​​the composite material. Studies have shown that combining them with carbon materials can form a stable structure and synergistic catalytic effect, resulting in a significant catalytic effect in the combustion field. Summary of the Invention

[0006] The purpose of this invention is to provide a low-cost and simple-to-prepare two-dimensional metal oxide composite reduced graphene oxide combustion rate catalyst. The catalyst uses a solvothermal method to combine reduced graphene oxide with two-dimensional metal oxide nanosheets to form a stable 2D-2D structure. The high electrical conductivity and good mechanical properties of reduced graphene oxide are utilized to enhance the synergistic catalytic effect and electron transfer rate of the metal oxide and carbon materials, thereby increasing the catalytic effect on AP.

[0007] The two-dimensional metal oxide composite reduced graphene oxide combustion rate catalyst provided by the present invention is prepared by the following method: two-dimensional metal oxide nanosheets and reduced graphene oxide are added to a solvent and ultrasonically dispersed, and then transferred to a high-pressure hydrothermal reactor for solvothermal reaction. The resulting precipitate is centrifuged, washed, and vacuum dried to obtain the combustion rate catalyst.

[0008] The two-dimensional metal oxide nanosheets mentioned above are any one of Co3O4, Cr2O3, NiO, Fe2O3, and CuO.

[0009] Furthermore, the preferred mass ratio of the two-dimensional metal oxide nanosheets to reduced graphene oxide is 1:0.5 to 3.

[0010] The preparation method of the above-mentioned two-dimensional metal oxide nanosheets is as follows: glucose, ammonium nitrate, and metal nitrate are ground evenly in a ball mill, and then calcined in a high-temperature muffle furnace to form two-dimensional porous metal oxide nanosheets. Preferably, the mass ratio of glucose, ammonium nitrate, and metal nitrate is 4:5:0.2-1, the ball milling speed is 1200-3000 rpm, the ball milling time is 4-8 h, the calcination temperature is 450-650 °C, the calcination time is 10-60 min, and the calcination atmosphere is air.

[0011] The aforementioned reduced graphene oxide is obtained by reacting hydrazine hydrate with graphene oxide treated with a surfactant. The surfactant is any one of polydiallyldimethylammonium chloride, polyvinylpyrrolidone, or hexadecyltrimethylammonium bromide.

[0012] Furthermore, the solvent is preferably a mixture of isopropanol and deionized water in a volume ratio of 0.5 to 2:1.

[0013] Furthermore, the temperature of the solvothermal reaction is preferably 80–120°C and the time is preferably 4–15 h.

[0014] Furthermore, the vacuum drying temperature is preferably 60–80°C and the time is preferably 8–20 hours.

[0015] The preparation method of the two-dimensional porous transition metal oxide of the present invention is as follows: glucose, ammonium nitrate, and metal nitrate are ground evenly in a ball mill, and then calcined in a high-temperature muffle furnace to form a two-dimensional porous metal oxide. Preferably, the mass ratio of glucose, ammonium nitrate, and metal nitrate is 4:5:0.2–1; preferably, the ball milling speed is 1200–3000 rpm, the ball milling time is 4–8 h, the calcination temperature is 450–650 °C, the calcination time is 10–60 min, and the calcination atmosphere is air.

[0016] The beneficial effects of this invention are as follows:

[0017] 1. This invention combines two-dimensional metal oxide nanosheets and reduced graphene oxide via a solvothermal method, controlling the longitudinal scale of the metal oxide at the nanoscale to expose more surface active sites. Furthermore, the reduced graphene oxide used is surface-modified with surfactants, enabling better dispersion in water. In addition, the interaction between the surfactants and graphene functionalizes the graphene, facilitating further loading of two-dimensional metal oxide nanosheets. Combining this with two-dimensional metal oxide nanosheets increases the specific surface area and electron transfer rate of the composite combustion catalyst, thereby improving catalytic efficiency.

[0018] 2. The two-dimensional transition metal oxide and reduced graphene oxide used in this invention have good combustion catalytic performance. The composite material has the conductivity of carbon materials and the stability of metal oxides, which greatly improves the "synergistic catalytic effect" of reduced graphene oxide and two-dimensional transition metal oxide, thereby improving the combustion catalytic performance of AP.

[0019] 3. The preparation method of the two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst of the present invention is simple, low-cost, environmentally friendly, and can be mass-produced. Attached Figure Description

[0020] Figure 1 This is a scanning electron microscope image of the reduced graphene oxide in Example 1.

[0021] Figure 2 This is a scanning electron microscope image of the two-dimensional Co3O4 nanosheets in Example 1.

[0022] Figure 3 This is a scanning electron microscope image of the two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst prepared in Example 1.

[0023] Figure 4 The differential scanning calorimetry (DSC) curves are obtained by adding 5 wt.% of the combustion rate catalyst prepared in Examples 1-5 to AP and pure AP, respectively.

[0024] Figure 5Differential scanning calorimetry (DSC) curves of combustion rate catalysts prepared by adding 5 wt.% of comparative examples 1–6 to AP and pure AP, respectively.

[0025] Figure 6 Differential scanning calorimetry (DSC) curves of the combustion rate catalysts prepared by adding 5 wt.% of Examples 1, 6, 7, and 8 to AP and pure AP, respectively.

[0026] Figure 7 Differential scanning calorimetry (DSC) curves of AP with 5 wt.% of the reduced graphene oxide from Example 1, the two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst, the combustion rate catalyst of Comparative Example 1, and pure AP were obtained. Detailed Implementation

[0027] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited to these embodiments.

[0028] Example 1

[0029] 1 mL of polydiallyldimethylammonium chloride was added to 50 mL of a 1 mg / mL aqueous solution of graphene oxide. The mixture was ultrasonically dispersed for 2 hours at 720 W and 20 °C. Then, 0.3 mL of hydrazine hydrate was added, and the mixture was stirred at 500 rpm and 90 °C for 3 hours. The mixture was filtered and washed with deionized water. The resulting solid was then vacuum-dried at 60 °C to obtain reduced graphene oxide, denoted as rGO. Figure 1 It can be seen that the prepared reduced graphene oxide has a wrinkled two-dimensional sheet structure on its surface, with some areas being transparent and the edges exhibiting a wavy or curled morphology, indicating that it has good flexibility.

[0030] 0.4 g glucose, 0.5 g ammonium nitrate, 0.02 g Co(NO3)2·6H2O, and 20 μL deionized water were placed in an agate ball mill jar and ball-milled at 2100 rpm for 6 h to obtain a uniform viscous precursor. The precursor was then calcined in a muffle furnace at 500 °C in an air atmosphere for 20 min, followed immediately by cooling to room temperature to obtain two-dimensional Co3O4 nanosheets. Figure 2 It can be seen that the prepared Co3O4 exhibits flexible and rolled nanosheets, a two-dimensional nanoscale structure composed of uniform nanoparticles, with the thickness of the nanosheets distributed in the range of 20-40 nm. The pore structure between particles is visible in some areas, indicating that the material has a porous structure.

[0031] 10 mg of two-dimensional Co3O4 nanosheets were added to 20 mL of isopropanol and ultrasonically dispersed for 20 min to obtain suspension A1. Then, 10 mg of rGO was added to 20 mL of deionized water and ultrasonically dispersed for 60 min to obtain suspension B1. Suspension B1 was then added to suspension A1 and ultrasonically mixed thoroughly. The mixture was then transferred to a 50 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene for a solvothermal reaction at 100 °C for 6 h. After the reaction, the mixture was allowed to cool naturally to room temperature and centrifuged at 10000 rpm. The resulting solid was then vacuum-dried at 80 °C for 6 h to obtain a two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst, denoted as Co3O4 / rGO-1. Figure 3 It can be seen that the reduced graphene oxide sheets are tightly bonded to the Co3O4 nanosheets, with no obvious gaps or severe stacking.

[0032] Example 2

[0033] In this embodiment, two-dimensional Cr2O3 nanosheets were prepared according to the method of Example 1, and the two-dimensional Co3O4 nanosheets in Example 1 were replaced with an equal amount of two-dimensional Cr2O3 nanosheets. The specific steps and conditions were the same as in Example 1, and a two-dimensional Co3O4 nanosheet composite reduction graphene oxide combustion rate catalyst was prepared, denoted as Cr2O3 / rGO.

[0034] Example 3

[0035] In this embodiment, two-dimensional NiO nanosheets were prepared according to the method of Example 1, and the two-dimensional Co3O4 nanosheets in Example 1 were replaced with an equal amount of two-dimensional NiO nanosheets. The specific steps and conditions were the same as in Example 1, and a two-dimensional NiO nanosheet composite reduction graphene oxide combustion rate catalyst was prepared, denoted as NiO / rGO.

[0036] Example 4

[0037] In this embodiment, two-dimensional Fe2O3 nanosheets were prepared according to the method of Example 1, and the two-dimensional Co3O4 nanosheets in Example 1 were replaced with an equal amount of two-dimensional Fe2O3 nanosheets. The specific steps and conditions were the same as in Example 1, and a two-dimensional Fe2O3 nanosheet composite reduction graphene oxide combustion rate catalyst was prepared, denoted as Fe2O3 / rGO.

[0038] Example 5

[0039] In this embodiment, two-dimensional CuO nanosheets were prepared according to the method of Example 1, and the two-dimensional Co3O4 nanosheets in Example 1 were replaced with an equal amount of two-dimensional CuO nanosheets. The specific steps and conditions were the same as in Example 1, and a two-dimensional CuO nanosheet composite reduction graphene oxide combustion rate catalyst was prepared, denoted as CuO / rGO.

[0040] Comparative Example 1

[0041] 0.4 g glucose, 0.5 g ammonium nitrate, 0.02 g Co(NO3)2·6H2O, and 20 μL deionized water were placed in an agate ball mill jar and ball-milled at 2100 rpm for 6 h to obtain a homogeneous viscous precursor. The precursor was then calcined in a muffle furnace at 500 °C in an air atmosphere for 20 min, followed immediately by cooling to room temperature to obtain a two-dimensional Co3O4 nanosheet combustion rate catalyst.

[0042] Comparative Example 2

[0043] 10 mg of two-dimensional Co3O4 nanosheets prepared in Comparative Example 1 and 10 mg of rGO prepared by the method in Example 1 were ground evenly in an agate mortar to obtain a mechanically mixed two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst.

[0044] Comparative Example 3

[0045] In Comparative Example 1, Co(NO3)2·6H2O was replaced with Cr(NO3)3·6H2O, and the other steps were the same as in Comparative Example 1, resulting in a dark green fluffy solid, namely a two-dimensional Cr2O3 nanosheet combustion rate catalyst.

[0046] Comparative Example 4

[0047] In Comparative Example 1, Co(NO3)2·6H2O was replaced with Ni(NO3)2·6H2O, and the other steps were the same as in Comparative Example 1, resulting in a gray, fluffy solid, namely a two-dimensional NiO nanosheet combustion rate catalyst.

[0048] Comparative Example 5

[0049] In Comparative Example 1, Co(NO3)2·6H2O was replaced with Fe(NO3)3·9H2O, and the other steps were the same as in Comparative Example 1, resulting in a reddish-brown fluffy solid, namely a two-dimensional Fe2O3 nanosheet combustion rate catalyst.

[0050] Comparative Example 6

[0051] In Comparative Example 1, Co(NO3)2·6H2O was replaced with Cu(NO3)2·6H2O, and the other steps were the same as in Comparative Example 1, resulting in a black, fluffy solid, namely a two-dimensional CuO nanosheet combustion rate catalyst.

[0052] Example 6

[0053] In Example 1, 10 mg of two-dimensional Co3O4 nanosheets were added to 20 mL of isopropanol and ultrasonically dispersed for 20 min to obtain suspension A1. Then, 5 mg of rGO was added to 20 mL of deionized water and ultrasonically dispersed for 60 min to obtain suspension B1. Suspension B1 was then added to suspension A1 and ultrasonically mixed evenly. The mixture was then transferred to a 50 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene for a solvothermal reaction at 100 °C for 6 h. After the reaction was complete, the mixture was naturally cooled to room temperature and centrifuged at 10,000 rpm. The resulting solid was vacuum dried at 80 °C for 6 h to obtain a two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst, denoted as Co3O4 / rGO-0.5.

[0054] Example 7

[0055] In Example 1, 10 mg of two-dimensional Co3O4 nanosheets were added to 20 mL of isopropanol and ultrasonically dispersed for 20 min to obtain suspension A1. Then, 20 mg of rGO was added to 20 mL of deionized water and ultrasonically dispersed for 60 min to obtain suspension B1. Suspension B1 was then added to suspension A1 and ultrasonically mixed evenly. The mixture was then transferred to a 50 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene for a solvothermal reaction at 100 °C for 6 h. After the reaction was complete, the mixture was naturally cooled to room temperature and centrifuged at 10,000 rpm. The resulting solid was vacuum dried at 80 °C for 6 h to obtain a two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst, denoted as Co3O4 / rGO-2.

[0056] Example 8

[0057] In Example 1, 10 mg of two-dimensional Co3O4 nanosheets were added to 20 mL of isopropanol and ultrasonically dispersed for 20 min to obtain suspension A1. Then, 30 mg of rGO was added to 20 mL of deionized water and ultrasonically dispersed for 60 min to obtain suspension B1. Suspension B1 was then added to suspension A1 and ultrasonically mixed evenly. The mixture was then transferred to a 50 mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene for a solvothermal reaction at 100 °C for 6 h. After the reaction was complete, the mixture was naturally cooled to room temperature and centrifuged at 10,000 rpm. The resulting solid was vacuum dried at 80 °C for 6 h to obtain a two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst, denoted as Co3O4 / rGO-3.

[0058] To demonstrate the effectiveness of this invention, combustion catalytic performance was tested by adding 5 wt.% reduced graphene oxide, the combustion rate catalysts prepared in Comparative Examples 1-6, and five two-dimensional metal oxide composite reduced graphene oxide combustion rate catalysts prepared in Examples 1-8 to AP. The results are shown in [Figure Number]. Figures 4-6 .

[0059] from Figure 4 As can be seen, when 5 wt.% of the two-dimensional metal oxide composite reduced graphene oxide combustion rate catalyst prepared in Examples 1-5 was added to the main component AP of the solid propellant, the high-temperature decomposition peak of AP was advanced from 417.1℃ to 293.9℃, 312.9℃, 326.1℃, 328.9℃, and 320.4℃, respectively, and decreased by 123.2℃, 104.2℃, 91.0℃, 88.2℃, and 96.7℃, respectively. The heat release of AP decreased from 739.39 J·g -1 Increased to 1512.95 J·g -1 1543.06 J·g -1 1718.89 J·g -1 1619.80 J·g -1 1598.49 J·g -1 The increases were 773.56 J·g respectively. -1 803.67 J·g -1 979.5 J·g -1 880.41 J·g -1 859.1 J·g -1 Among them, Co3O4 / rGO showed the greatest advance in the high-temperature decomposition peak of AP thermal decomposition catalysis and produced a larger amount of heat release. Furthermore, the peak shape revealed a more concentrated heat release. After adding 5 wt.% of the two-dimensional metal oxide composite reduced graphene oxide combustion rate catalyst prepared in Examples 1-5, the high-temperature decomposition stage of AP exhibited a concentrated heat release phenomenon, and the amount of heat released increased significantly, indicating that the combustion rate catalyst of this invention has a good combustion catalytic effect on the thermal decomposition of AP.

[0060] from Figure 5 It can be seen that, under the same conditions, when 5 wt.% of the two-dimensional metal oxide combustion rate catalysts prepared in comparative examples 1, 3, 4, 5, and 6 were added to the main component AP of the solid propellant, the high-temperature decomposition peak of AP was advanced. Among them, the peak temperature of two-dimensional Co3O4 nanosheets advanced the most, with the high-temperature decomposition peak of AP advancing from 417.1℃ to 302.5℃, and the heat release increasing from 739.39 J·g -1 Increased to 1420.41 J·g -1 It increased by 681.02 J·g -1 When 5 wt.% of the mechanically mixed two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst prepared in Comparative Example 2 was added to the main solid propellant component AP, the high-temperature decomposition peak of AP was advanced to 318.3℃, and the heat release increased by 928.85 J·g. -1The DSC curves clearly show that the exothermic peak is broadened and the exothermic effect is not concentrated, indicating that the physical mixing did not achieve the ideal composite effect. The peak temperature of the catalyst for reducing graphene oxide combustion rate prepared by the solvothermal method in Example 1 is shifted by 24.4℃, and the peak temperature of the two-dimensional Co3O4 nanosheets in Comparative Example 1 is shifted by 15.8℃. This indicates that mechanical grinding destroyed the original two-dimensional structure of the oxide, resulting in a poorer catalytic effect.

[0061] from Figure 6 It can be seen that, under the same conditions, when 5 wt.% of the two-dimensional Co3O4 nanosheet composite reduced graphene oxide combustion rate catalyst prepared in Examples 1, 6, 7, and 8 is added to the main component AP of the solid propellant, the high-temperature decomposition peak of AP is advanced from 417.1℃ to 293.9℃, 297.6℃, 297.4℃, and 325.6℃, respectively, and reduced by 123.2℃, 119.5℃, 119.7℃, and 91.5℃, respectively. The heat release of AP is reduced from 739.39 J·g -1 Increased to 1512.95 J·g -1 1431.51 J·g -1 1602.81 J·g -1 1816.25 J·g -1 The increases were 773.56 J·g respectively. -1 692.12 J·g -1 863.42 J·g -1 1076.86 J·g -1 The results showed that as the rGO content in the combustion rate catalyst increased, the heat release gradually increased, and the decrease in peak temperature showed a trend of first increasing and then decreasing. Among them, Co3O4 / rGO-1 had the highest relative catalytic activity for AP.

[0062] from Figure 7 It can be seen that, under the same conditions, when 5 wt.% of the burning rate catalyst of Example 1, as well as reduced graphene oxide and the burning rate catalyst of Comparative Example 1, are added to the main component AP of the solid propellant, the high-temperature decomposition peak of AP is advanced from 417.1℃ to 293.9℃, 341.1℃, and 302.5℃, respectively, representing reductions of 123.2℃, 76℃, and 114.6℃, respectively. The heat release of AP is reduced from 739.39 J·g -1 Increased to 1512.95 J·g -1 1219.61 J·g -1 1420.41 J·g -1 The increases were 773.56 J·g respectively. -1 480.22 J·g -1 681.02 J·g -1Compared to the burning rate catalyst of Example 1, the catalytic effect of reduced graphene oxide and the burning rate catalyst of Comparative Example 1 is not as obvious. This indicates that the composite of reduced graphene oxide and two-dimensional Co3O4 nanosheets is not a simple mechanical mixture of the two, but rather a synergistic catalytic effect between the two through a solvothermal composite method.

Claims

1. A two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst, characterized in that: The combustion rate catalyst is composed of two-dimensional metal oxide nanosheets and reduced graphene oxide through a solvothermal reaction, forming a stable 2D-2D structure. The method for preparing the combustion rate catalyst is as follows: two-dimensional metal oxide nanosheets and reduced graphene oxide are added to a solvent and ultrasonically dispersed, then transferred to a high-pressure hydrothermal reactor for solvothermal reaction, and the resulting precipitate is centrifuged, washed, and vacuum dried to obtain the combustion rate catalyst. The preparation method of the two-dimensional metal oxide nanosheets is as follows: glucose, ammonium nitrate and metal nitrate are put into a ball mill and ground evenly, and then calcined in a high-temperature muffle furnace to form two-dimensional porous metal oxide nanosheets. The two-dimensional metal oxide nanosheets are any one of Co3O4, Cr2O3, NiO, Fe2O3, and CuO.

2. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 1, characterized in that: The mass ratio of glucose, ammonium nitrate, and metal nitrate is 4:5:0.2-1; the ball milling speed is 1200-3000 rpm, the ball milling time is 4-8 h, the calcination temperature is 450-650 ℃, the calcination time is 10-60 min, and the calcination atmosphere is air.

3. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 1, characterized in that: The reduced graphene oxide is obtained by reacting hydrazine hydrate with a surfactant-treated graphene oxide.

4. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 3, characterized in that: The surfactant is any one of polydiallyldimethylammonium chloride, polyvinylpyrrolidone, and hexadecyltrimethylammonium bromide.

5. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 1, characterized in that: The mass ratio of the two-dimensional metal oxide nanosheets to the reduced graphene oxide is 1:0.5 to 3.

6. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 1, characterized in that: The solvent is a mixture of isopropanol and deionized water in a volume ratio of 0.5 to 2:

1.

7. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 1, characterized in that: The solvothermal reaction is carried out at a temperature of 80–120 °C for a time of 4–15 h.

8. The two-dimensional metal oxide composite reduction graphene oxide combustion rate catalyst according to claim 1, characterized in that: The vacuum drying temperature is 60–80 °C and the time is 8–20 h.

Citation Information

Patent Citations

  • Polydiallyldimethyl ammonium chloride and graphene hybridized nano modification material and preparation method and application thereof

    CN108732220A

  • Ammonium perchlorate thermal decomposition catalytic material and preparation method thereof

    CN111774063A

  • Preparation method of two-dimensional non-layered metal oxide porous nanosheet

    CN114702011A

  • Graphene-loaded MgO catalyst as well as preparation method and application thereof

    CN118580132A